Conceptualizing the Contribution of Green Human Resource Management in Strengthening Institutional Networking for Sustainable Agribusiness in Indonesia - Nabila, Putri Dam'un (Generate Digital Publishing, 2025)
Objective: This study aims to explore the strategic convergence between Green Human Resource Management (GHRM), Institutional Networks, and Green Dynamic Capabilities (GDC) in enhancing the sustainability and competitiveness of agribusiness organizations in developing countries. The main objective of this study is to develop an integrative framework that aligns internal processes, external collaboration, and adaptive capabilities to respond to environmental and market uncertainties in a sustainable manner. Research Design & Methods: This study employs a Systematic Literature Review (SLR) of 65 articles (2015–2024) to explore the links between GHRM, institutional networks, and Green Dynamic Capabilities (GDC) in agribusiness using thematic analysis, following PRISMA guidelines for rigor and transparency. Findings: The results of the study show that GHRM functions as an internal catalyst in shaping a pro-environmental organizational culture, while institutional networks provide an external platform for social legitimacy, policy synchronization, and knowledge exchange. GDC acts as a connector that enables organizations to effectively sense, seize, and reconfigure opportunities and resources. The synergistic interaction of these three elements strengthens organizational resilience, promotes sustainable value creation, and enhances the competitiveness of agribusiness in a dynamic environment. Implications & Recommendations: This study emphasizes the importance of institutionalizing Green Human Resource Management (GHRM) practices in agribusiness to encourage ecological innovation. GHRM needs to be strengthened through cross-stakeholder collaboration and dynamic capability development. Public policy should support the strengthening of the role of green human resources in building sustainable agribusiness in various geographical contexts. Contribution & Value Added: This study enriches the literature on sustainability management by proposing an integrative framework that links green HRM practices (micro), institutional engagement (meso), and strategic adaptation (macro), and combines the RBV, Institutional Theory, and Dynamic Capabilities approaches to support sustainable agribusiness transformation.